(3eYHQ GdHMQjf (B( (3aj Hfi OjeGf (B)s ((3ehQJjGfjG s)
(3ChdgG (B:s
(3fXeJg def HOjfg CMJad hWHYg hef ShGge CHJgd s
(3BNQgG (B:s
(3CMeO ef QSd Gddg gfG NJe hUGHg fhQ GdfHhAI hbe s
(3GdfSNI HgG MhGTs
(3bUjOI ai JGQjN Hfi OjeGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs